2021
DOI: 10.1186/s12889-021-10790-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, behaviours and barriers to public health measures for COVID-19: a survey to inform public health messaging

Abstract: Background Public support of public health measures including physical distancing, masking, staying home while sick, avoiding crowded indoor spaces and contact tracing/exposure notification applications remains critical for reducing spread of COVID-19. The aim of our work was to understand current behaviours and attitudes towards public health measures as well as barriers individuals face in following public health measures. We also sought to identify attitudes persons have regarding a COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 28 publications
4
48
0
5
Order By: Relevance
“…We considered factors that could be associated with vaccine hesitancy in each of the domains of the SAGE framework (contextual influences, individual and group influences, and vaccine-specific factors) [ 8 ] based on a review of the literature, focus groups [ 4 ], and a pilot survey [ 5 ] that we completed in Alberta, Canada in the summer of 2020. For contextual influences, we determined demographic factors, including sex, age, geographical region, household income, highest level of education, ethnicity, and political leaning.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We considered factors that could be associated with vaccine hesitancy in each of the domains of the SAGE framework (contextual influences, individual and group influences, and vaccine-specific factors) [ 8 ] based on a review of the literature, focus groups [ 4 ], and a pilot survey [ 5 ] that we completed in Alberta, Canada in the summer of 2020. For contextual influences, we determined demographic factors, including sex, age, geographical region, household income, highest level of education, ethnicity, and political leaning.…”
Section: Methodsmentioning
confidence: 99%
“…In the summer of 2020, we designed a mixed methods study to examine COVID-19 attitudes, beliefs, and behaviors among Canadians with an overreaching goal of informing targeted public health messaging to improve adherence to NPIs and vaccine uptake. We have previously published the initial phases of this mixed methods study including a pilot survey [ 5 ] and a qualitative study [ 4 ]. This preliminary work found that there were mixed views regarding willingness to take a COVID-19 vaccine and identified a number of risk factors with respect to COVID-19 vaccine hesitancy, including low perceived risk of COVID-19 infection, vaccine-specific concerns, low adherence to NPIs, and sources of COVID-19 information [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 ) was used to assess respondents’ self-reported adherence to NPIs including physical distancing, masking, avoiding public spaces and staying home when sick as methods to reduce spread of COVID-19. This survey was informed by an online survey and focus groups conducted in Alberta, Canada by the research team 57 , 58 . Information on sociodemographic factors, attitudes towards COVID-19 and NPIs as well as risk and trust measures were collected.…”
Section: Methodsmentioning
confidence: 99%